Drug-Induced Impulse Control Disorders: A Review - Atmaca, Murad (Bentham Science Publ Ltd, 2014)
The essential characteristic of impulse disorders is the failure to resist an impulse, drive or temptation to perform an act that is harmful to the person or to others. Clearly, impulse control disorders can occur without an induction of any drugs, and they may lead to very problematic situations that affect the adjustment of the patient and need to be treated immediately. However, the subject of the present review is impulsivity induced by a variety of drugs. In this context, the most frequently established agents are dopaminergic agonists that may affect the mesolimbic dopaminergic pathway, such as cocaine and methamphetamine. In Parkinson's disease, the triggering effect of levodopa on pounding has been known since the first description of the condition by Friedman. In this paper, we reviewed the role of a variety of psychopharmacological agents, including dopaminergic ones on the occurrence of impulse control disorders, by searching the PubMed database for relevant articles published in the period between 1980 and 2012 August in detail.
Keywords: Impulse control disorders; dopaminergic agents; pathological gambling